An Insight into the Role of Postmortem Immunohistochemistry in the Comprehension of the Inflammatory Pathophysiology of COVID-19 Disease and Vaccine-Related Thrombotic Adverse Events: A Narrative Review - Chiara Stassi (MDPI AG, 2021)
On 11 March 2020, the World Health Organization (WHO) declared a pandemic due to the spread of COVID-19 from Wuhan, China, causing high mortality rates all over the world. The related disease, which mainly affects the lungs, is responsible for the onset of Diffuse Alveolar Damage (DAD) and a hypercoagulability state, frequently leading to Severe Acute Respiratory Syndrome (SARS) and multiorgan failure, particularly in old and severe-critically ill patients. In order to find effective therapeutic strategies, many efforts have been made aiming to shed light on the pathophysiology of COVID-19 disease. Moreover, following the late advent of vaccination campaigns, the need for the comprehension of the pathophysiology of the fatal, although rare, thrombotic adverse events has become mandatory as well. The achievement of such purposes needs a multidisciplinary approach, depending on a correct interpretation of clinical, biochemical, biomolecular, and forensic findings. In this scenario, autopsies have helped in defining, on both gross and histologic examinations, the main changes to which the affected organs undergo and the role in assessing whether a patient is dead “from” or “with” COVID-19, not to mention whether the existence of a causal link exists between vaccination and thrombotic adverse events. In the present work, we explored the role of postmortem immunohistochemistry, and the increasingly used ancillary technique, in helping to understand the mechanism underlying the pathophysiology of both COVID-19 disease and COVID-19 vaccine-related adverse and rare effects.